The case of the bizarre bouquets eaudiobook - Springer, Nancy (Enola Holmes, 2008)
Don't miss Enola Holmes: The Case of the Missing Marquess! A Netflix original movie starring Millie Bobby Brown, Henry Cavill, and Helena Bonham Carter! Enola Holmes—younger sister to Sherlock Holmes—is back on another case! Everyone knows Dr. Watson is Sherlock Holmes's right-hand man, so when he goes missing, it's a shock. Even Sherlock hasn't the slightest clue as to where he could be. Enola is intrigued but wary; she's still hiding from her older brothers, and getting involved could prove to be disastrous. But Enola can't help but investigate, especially when she learns that a bizarre bouquet—with flowers all symbolizing death—has been delivered to the Watson residence. Enola knows she must act quickly, but can she find Dr. Watson in time?